Additional file 2 of Phylogenetic analysis of the caspase family in bivalves: implications for programmed cell death, immune response and development - Susanne Vogeler (3428648); Stefano Carboni (2339416); Xiaoxu Li (12771); Alyssa Joyce (721836) (2021)
Additional file 2: Alignments of full protein and coding sequence CDS sequences of Crassostrea gigas caspase homologues: caspase-1 [12], caspase-1 [31], caspase-3 [32] and Cg3B (identified in this study).